A new species of Austrothaumalea Tonnoir from Australia (Diptera: Thaumaleidae) - Pivar, Robert J.; Moulton, John K.; Sinclair, Bradley J. (Zootaxa, 2016)
Austrothaumalea spiculata sp. nov. is described from Grampians National Park, in southwest Victoria (Australia). It is known only from the type series and is the second species of Thaumaleidae recorded from the Park. Illustrations of the male terminalia, as well as a distribution map, are provided. Phylogenetic affinities are hypothesized and an updated species identification key is offered.